Identification of risk factors for collisions involving cyclists based on Gdansk example - Okraszewska, Romanika; Jamroz, Kazimierz; Bauer, Marek; Birr, Krystian; Gobis, Anna (International Conference “Environmental Engineering”, 2017)
The role of pedestrian and bicycle traffic in Poland has growing trend. The comprehensive traffic study, conducted in Gdansk in 2016, has confirmed the increase in the number of cyclists and their share in the modal split. Therefore, it is particularly important to ensure the safety of this group of unprotected road users. Only in 2015 on the roads of Gdansk occurred 93 accidents (excluding collisions) involving cyclists. As a result, 101 people were injured, including nine seriously and 3 people killed. The study aim was to identify risk factors for collisions involving cyclists based on data of accidents reported to the police. The following factors were analysed: the conditions for the drivers on the road (speed limits of, surface conditions), conditions for cyclists (cycling infrastructure, traffic management), external conditions (time of the year, time of the day, weather conditions), conditions organizational (type of intersection, traffic light) as well as the social aspects – the behaviour of all users.
Keywords: vulnerable road users; risk factors; cycle infrastructure